942. Pulmonary Infections in Intestinal Transplant Recipients with Preexisting Pulmonary Nodules. (4th December 2021) - Cardenas, Jorge; Natori, Yoichiro; Anjan, Shweta; Vianna, Rodrigo; Garcia, Jennifer; Simkins, Jacques
Abstract: Background: Pulmonary nodules in asymptomatic patients could represent latent pulmonary infections. Intestinal transplant (ITx) recipients with preexisting pulmonary nodules might be at higher risk for pulmonary infections. However, data is lacking. Methods: This retrospective study included adult patients that underwent intestinal transplantation (ITx) from 5/2016 to 5/2020. Chest computed tomography (CT) scans performed within 12 months prior of ITx were obtained to evaluate for preexisting pulmonary nodules. Screening for endemic mycoses, Aspergillus, Cryptococcus and latent tuberculosis infection (LTBI) performed within 12 months prior ITx was obtained. We assessed for worsening pulmonary nodules, and fungal and mycobacterial infections during the 1 st year post-transplant. Survival at one year post-transplant was also assessed. Results: Forty-three patients underwent ITx. Twenty-three (53%) were Female. Median age was 46 years (range: 18-67). Chest CT scans were performed in 36(84%) patients prior to ITx. Preexisting pulmonary nodules were found in 30 (83%) of the patients. All were asymptomatic. Nodules were not calcified in 10 (33%) patients, calcified in 4 (13%), some calcified and some not calcified in 4 (13%) and unclear in 12 (40%). All the patients screened negative for fungi [ Coccidioides antibody (Ab) was done in 15 (50%) patients, Blastomyces Ab and Histoplasma Ab in 7 (23%) each, Histoplasma urine antigen (Ag) and Aspergillus serum galactomannan in 3 (10%) each, and Cryptococcus serum Ag in 10 (33%) patients]. QuantiFERON-TB (QFT) was negative in 35 (81%) patients, positive in 2 (5%) and indeterminate in 6 patients (14%). QFT-Gold In-Tube was replaced to QFT-Plus in 3/2019. Post-transplant worsening of pulmonary nodules was noted in 12 (40%) patients and bronchoscopy was performed in six of them. Note that only 1 (3%) of the patients that had pre-existing pulmonary nodules developed a pulmonary infection (invasive pulmonary aspergillosis diagnosed 33 days after ITx). Our cohort survival at one year post-transplant was 79%. Conclusion: Preexisting pulmonary nodules was common in our ITx cohort. However, only one case of pulmonary infection was noted among those who had preexisting pulmonary nodules. Clinical monitoring is essential. Disclosures: All Authors : No reported disclosures